Physical Characteristics and Germination Testing Methods of Turi (Sesbania grandiflora (L.) Pers) Seeds - Eliya Suita; Dida Syamsuwida (Jurnal Perbenihan Tanaman Hutan, 2017)
Turi (Sesbania grandiflora (L.) Pers) is belong to Leguminosae which is a species of non-timber product   utilized as food, energy, medicine, fodder and others. Turi seed has a hard coat, so that to get a maximum germination, it’s required pre-treatments before the seeds are sown. The objective of the study was to determine the physical characteristics of the seeds, and  the approriate of pre-treatments methods to find out the viability  of turi seeds. Physical characteristics are examining the  water content and  weight of 1000 seeds. The pre-treatments including: 24 hours water soaked seeds, hot water soaked seeds (temperature1000C) and let them cooler for 24 hours, 10 minutes sulfuric acid soaked seeds, 20 minutes sulfuric acid soaked seeds and no treatment. Viability examination methods consisted of the testing of top of paper, between paper and standed-pleated paper. The tested using  opened soil-sand (v/v 1:1) mixture media and closed soil-sand (v/v 1:1) mixture media. The best pre-treatment that are enable to increase the viability of turi seeds are seeds soaked with sulfuric acid for 20 minutes and sown in a laboratory by using testing methods of either top of paper or standed plated of paper placed in a germinator.